History can bite : history education in divided and postwar societies - Bentrovato, Denise HerausgeberIn; Korostelina, Karina V. HerausgeberIn; Schulze, Martina HerausgeberIn; V & R unipress GmbH (Eckert, 2016)
Introduction -- Textbooks and curricula as tools for nation-building: between inclusion and exclusion -- Cultures of silence: forging invaluable lessons from a violent past -- Integrating the topics of war and peace into the classroom: teacher and student voices and experiences